"Then and Now": Examining the Impact of Temporal Focus on Persuasive Messages across Seniors and Young Adults. Issue 1 (1st January 2021) - Imtiaz, Faizan; Ji, Li-Jun
ABSTRACT: Background: As the number of seniors around the world continues to proliferate, research devoted to enhancing our understanding of the specific needs of these individuals is warranted. The present research documents how the concept of time influences the preferences and behavioral intentions of older and younger adults in a consumer behavior context. Methods: Study 1 had 99 young adults (under 25) and 82 seniors (over 65) rate persuasive advertisements varying in their temporal focus (past vs future vs control). Using a forced-choice paradigm, Study 2 had 98 young adults and 74 seniors choose between a product being advertised using a past versus future frame. Results: Study 1 indicated that seniors responded more favorably to advertisements presented with a past-focus compared to future-focused and control ads, while younger adults rated the control ads higher than both the past- and future-focused ones. Study 2 reported that seniors opted for a past-focused product more frequently (68%) than a future-focused alternative (32%), with younger adults showing no pattern in their choices. Conclusions: Seniors may respond more favorably to persuasive messages framed with a past temporal focus, in turn influencing their preferences and decision-making across several domains including consumer behavior, health promotion, and leadership.